Textural Characteristic, Antioxidant Activity, Sugar, Organic Acid, and Phenolic Profiles of 10 Promising Jujube (Ziziphus jujuba Mill.) Selections - Gao, Qing-Han; Wu, Chun-Sen; Yu, Jin-Gang; Wang, Min; Ma, Yu-Jie; Li, Cui-Li (Journal of food science, 2012)
:  Ten promising jujubes were analyzed for textural characteristic (hardness), antioxidant activity, sugar, organic acid, and phenolic profiles. Total phenolic content (TP) measured by Folin–Ciocalteu method ranged from 275.6 to 541.8 mg of gallic acid equivalents per 100 g fresh weight (mg GAE/100 g FW). Four sugars (rhamnose, fructose, sucrose, and glucose), 3 organic acids (malic, citric, and succinic acids), and 11 phenolic compounds (gallic acid, protocatechuic acid, cinnamic acid, chlorogenic acid, caffeic acid, ferulic acid, ellagic acid, catechin, epicatechin, rutin, and quercetin) were identified and quantified by high‐performance liquid chromatography in jujube fruits. The results showed that ascorbic acid and proanthocyanidins contents were positively correlated with hardness, and antioxidant activity was well correlated with TP content. Among 10 jujube cultivars, Zizyphus jujuba cv. Qingjianmuzao is good for direct consumption containing high levels of total soluble solids, total sugars, fructose, and glucose, while Zizyphus jujuba cv. Jiaxianmuzao could be an important dietary source of natural antioxidants. Practical Application:  Genotype is the main factor influencing the composition of bioactive compounds in jujubes. Zizyphus jujuba cv. Qingjianmuzao is good for direct consumption, while Zizyphus jujuba cv. Jiaxianmuzao could be an important dietary source of natural antioxidants for prevention of diseases caused by oxidative stress.